(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
From the plays of his middle phase (1926-1934), three plays, namely, The Great God Brown (1926), Strange Interlude (1928), Mourning Becomes Electra (1931), have been selected for the present study in the light of the ‘play’ of the unconscious or bad faith and the conscious. While in his early plays, O’Neill’s characters find it difficult to come out of their unconsciously cultivated desires or their bad faith, in the plays of his middle phase, they in the end, through their suffering, grow conscious, though not completely, the futility of their dreams, and indeed show signs of understanding of what it means to be living in bad faith.